(3JPcQI GdCdHGH HCUhd GdCfSGHs - (3GdHJj , CMeO Hf YHO GdYRjR Hf YHO Gdehdj, CHh LYaQ,J (B488 (3g` s
(3ChdgG (B:s
(3feQ VfG HYO MeO Gddg JYGdi hGdUdGI Ydi fHjg eMeO Udi Gddg Ydjg hSde Cf fLjH CMO LdI ChdjGFfG Edi eG QZH ajg s
(3BNQgG (B:s
(3hMSHfG Cf fba gGgfG hGdMeO ddg QH GdYGdejf s
(3Vef eLehY s
(3HJg (B: (3bQjI ef bQi HdfSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B151 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B276s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B86 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdJjehQjI (B(89) s
Keywords: (3GdJGQjNs